Archaeological analogues and corrosion prediction: from past to future. A review. (September 2014) - Dillmann, P.; Neff, D.; Féron, D.
<x content-type="archive" xml:space="preserve">Abstract</x> A new approach including the use of archaeological analogues is needed to predict corrosion phenomena over extended time periods lasting centuries to several millennia. The corrosion rates observed on analogues generally range from 0·1 to 10 μm/year, depending on the medium. Isotopic markers (deuterium or oxygen-18) can be used on archaeological objects to determine and localise the anodic and/or cathodic mechanisms. Modelling and simulation take into account statistical aspects (modelling by cellular automata) and kinetics, including localised corrosion phenomena (pitting factor).